Tunable photo-patterning of organic color-centers. (15th December 2021) - Dou, Qingqing; Xu, Beibei; Wu, Xiaojian; Mo, Junyao; Wang, YuHuang
Graphical abstract: Highlights: Photo-patterning strategy is developed to realize scalable localization of color-centers with high spatial accuracy. Light-stimulation can promote the functionalization of SWCNTs films forming organic color-centers. The patterns can be modulated by varying the chemical properties of the solvents. Abstract: Organic color-centers (OCCs) in single-walled carbon nanotubes (SWCNTs) have been intensively investigated for quantum technologies, bio- and chemical sensing, bioimaging. The precise localization of OCCs at a scalable manner will bring about a revolution into next generation optoelectronics, which, however, remains a great challenge till now. Here, a scalable, low cost and universal photo-patterning strategy is developed to implant OCCs at desired locations on (6, 5)-chirality SWCNT films by combining optically active diazonium chemistry and micro-contact printing methods. Notably, the patterns can be tunable by changing the solvents used for the patterning chemistry, affording control over the weight of diazonium salts at different regions. A systematic investigation reveals that the solvent properties (polarity and vapor pressure), the volume and concentration of ink used, the patterning methods, and the concentration of MeODz all contribute to the tunable patterning. This spatial accurate and solvent tunable photo-patterning technique is simple, scalable, and amenable to the integration of other color center chemistries and 2D transition metal dichalcogenides for the next-generation chip-integrated nanoelectronics and optoelectronics with high device uniformity and manipulability at molecular level.